Towards Digital Accountability: A Study of the Application of Information Technology in the Financial Reports of Palolo Village - Nelson Andresanto Jonathan; Muslimin; Yunus Kasim; Rian Risendy (PT. Global World Scientific, 2025)
This study aims to analyze the application of information technology in the preparation of village financial reports in Palolo District, Sigi Regency. The independent variable in this study is the application of information technology (Siskeudes), while the dependent variable is the preparation of village financial reports. The population in this study were village governments from six villages in Palolo District, with six respondents as the research sample. Respondents consisted of village officials directly involved in financial management, especially the village treasurer. Data collection techniques used were interviews and documentation, while data analysis techniques used a qualitative approach through three stages: data reduction, data presentation, and conclusion drawing. The research results indicate that the application of information technology in the preparation of village financial reports in Palolo District has not been optimal. Key obstacles include unstable internet access and a lack of understanding among village officials regarding the use of the Siskeudes application. This situation hinders the effectiveness and efficiency of village financial reporting and highlights the need for increased capacity and infrastructure to support the comprehensive digitalization of village financial governance.